Penerapan Analytical Hierarchy Process Dalam Desain User Experience Aplikasi Learning Management System - Utami, Sri; Fitriani, Yuni (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2022)
The application of the analytic hierarchy process (AHP) method in the interest of proving the criteria that are the key to the successful realization of user experience in an application. Seeing the many applications of the AHP method both in the system and in management, it is proven to be able to assist in the decision-making process objectively. The AHP method covers the data collection and analysis stages. For data collection, this study uses an online questionnaire method by utilizing a google form containing questions related to the success factors that affect the application of the learning management system. Respondents are random, the results are recapitulated by looking at the answers that are more chosen from each question. The total of the answers is processed to substantiate that the selected criteria are indeed well correlated with each other, by first completing the calculation in the form of a matrix with certain patterns using the AHP method.